On the classification and reduced equations of the second order linear partial differential equations in two independent variables - Safak, Suleyman (Fırat University, 2016)
[Abstract Not Available]
İki Bağımsız Değişkenli İkinci Basamaktan Doğrusal Kısmi Diferansiyel Denklemlerin Sınıflandırılması ve İndirgenmiş Denklemeleri Üzerine